PENGARUH INTELLECTUAL CAPITAL, PENGUNGKAPAN INTELLECTUAL CAPITAL DAN KARAKTERISTIK PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Sriastutik, Wahyu; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This researchis aimed to examine the influence of intellectual capital, intellectual capital disclosure, andcorporate characteristics to the firm value, through annual report which has been prepared by the LQ-45companies in 2012-2015 periods which are listed in Indonesia Stock Exchange (IDX). The corporatecharacteristics in reflected by several indicators, i.e.: firm size, leverage, profitability, and firm age. Thepopulation has been obtained by using purposive sampling method to the LQ-45 companies which are listed inIndonesia Stock Exchange (IDX) from February 2013 to February 2016. Based on the predetermined criteria, 25companies in 2012-2015 periode have been selected as samples. So, 100 sample companies have been used as thecircular. The analysis method has been carried out by using multiple linear regressions analysis and the SPSS(Statistical Product and Service Solutions) application tool. The result of t test shows that intellectual capitaland firm size give negative influence to the firm value. The intellectual capital disclosure, leverage, andprofitabilily give positive influence to the firm value. Mean while, firm age does not give any influence to thefirm value.Keywords: Intellectual capital, intellectual capital disclosure, corporate characteristics, firm value.